Respuestas
Respuesta dada por:
1
veamos
![y = \frac{-6+ \sqrt{ 6^{2}-4(-1)(7) } }{2*1} y = \frac{-6- \sqrt{6 ^{2}-4(-1)87)} }{2*1}<br /> y = \frac{-6+ \sqrt{ 6^{2}-4(-1)(7) } }{2*1} y = \frac{-6- \sqrt{6 ^{2}-4(-1)87)} }{2*1}<br />](https://tex.z-dn.net/?f=y+%3D+%5Cfrac%7B-6%2B+%5Csqrt%7B+6%5E%7B2%7D-4%28-1%29%287%29+%7D+%7D%7B2%2A1%7D+++++++++y+%3D++%5Cfrac%7B-6-+%5Csqrt%7B6+%5E%7B2%7D-4%28-1%2987%29%7D+%7D%7B2%2A1%7D%3Cbr+%2F%3E%C2%A0)
![y = \frac{-6 + \sqrt{36+28} }{2} y = \frac{-6 - \sqrt{36+28} }{2} y = \frac{-6 + \sqrt{36+28} }{2} y = \frac{-6 - \sqrt{36+28} }{2}](https://tex.z-dn.net/?f=+y+%3D++%5Cfrac%7B-6+%2B+%5Csqrt%7B36%2B28%7D+%7D%7B2%7D++++++++++++++++++++++++y+%3D++%5Cfrac%7B-6+-+%5Csqrt%7B36%2B28%7D+%7D%7B2%7D+)
![y = \frac{-6+ \sqrt{64} }{2} y = \frac{-6 - \sqrt{64} }{2}
y = \frac{-6+ \sqrt{64} }{2} y = \frac{-6 - \sqrt{64} }{2}](https://tex.z-dn.net/?f=y+%3D++%5Cfrac%7B-6%2B+%5Csqrt%7B64%7D+%7D%7B2%7D++++++++++++++++++y+%3D++%5Cfrac%7B-6+-+%5Csqrt%7B64%7D+%7D%7B2%7D+%0A)
![y = \frac{-6+8}{2} y = \frac{-6-8}{2} y = \frac{-6+8}{2} y = \frac{-6-8}{2}](https://tex.z-dn.net/?f=y+%3D++%5Cfrac%7B-6%2B8%7D%7B2%7D+++++++++++++++++++y+%3D++%5Cfrac%7B-6-8%7D%7B2%7D+)
![y = \frac{2}{2} y = \frac{-14}{2}
y = \frac{2}{2} y = \frac{-14}{2}](https://tex.z-dn.net/?f=y+%3D+%5Cfrac%7B2%7D%7B2%7D+++++++++++++++++++++++++++y+%3D++%5Cfrac%7B-14%7D%7B2%7D+%0A)
y = 1 y = -7
respuesta la B
y = 1 y = -7
respuesta la B
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años